Penggunaan Analisis Biplot dalam Pengelompokan Kabupaten/Kota di Provinsi Sulawesi Selatan Berdasarkan Indikator Kesejahteraan Masyarakat - Irwan; Sanusi, Wahidah; Nurani, Kahvi (Jurusan Matematika FMIPA UNM, 2023)
This study aims to group districts / cities in South Sulawesi Province in 2021 that havesimilarities in community welfare variables using biplot analysis. Biplot analysis is an effort to makeimages in many-dimensional space into images in two-dimensional space, some important informationthat can be obtained are: proximity between observed objects, variable diversity, correlation betweenvariables and variable values of an object. This research uses the SVD (Singular Value Decomposition)method, with a research object of 24 districts / cities in South Sulawesi Province and consists of 13indicator variables. Based on the results of the study, the districts/cities that have similar indicators ofcommunity welfare are divided into 4 groups, group 1 is Makassar City, Pinrang and Luwu Regencies,group 2 is Pangkajene and Islands, Wajo, Takalar, Bulukumba, Soppeng, Bone, Jeneponto, Gowa,Maros, Sirenreng Rappang and Barru, group 3 namely Sinjai, North Luwu, Selayar Islands and Bantaengand group 4 namely Parepare City, Palopo City, Tana Toraja, North Toraja, East Luwu and Enrekang.With the greatest diversity of community welfare indicators are expected years of schooling (X4) andaverage years of schooling (X5). The variables that influence each other and are positively correlated.Namely, expectation of years of schooling (X4) and using a cellular phone (HP) (X12).